Heavy Naphtha Desulfurization by Ozone Generated via the DBD Plasma Reactor - Abdullah, Noor M.; Hussien, Hussien Q.; Jalil, Rana R. (Iraqi Journal of Chemical and Petroleum Engineering, 2024)
This work presents an investigation into the ultra-desulfurization of heavy naphtha fuel (model using BT and DBT) using oxidation and solvent extraction techniques. Ozone produced by the DBD (Dielectric barrier discharge) plasma generator was employed in the oxidation process as an oxidant, and acetonitrile was used as a solvent extraction. Box-Behnken experimental design was adopted in the current study to examine oxidation desulfurization by non-thermal plasma for the various operation conditions including time, flow rate, and temperature on sulfur removal efficiency. Acetonitrile with an oxidized oil/solvent ratio of 1:1(v/v ratio) was utilized as the extraction solvent.  The results showed that the maximum sulfur removal of about 91% was obtained with a temperature of 50°C, flow rate of 75 ml/min, and time of 4 hours.